Management of asymptomatic, well-differentiated PNETs: results of the Delphi consensus process of the Americas Hepato-Pancreato-Biliary Association. Issue 5 (May 2019) - Mansour, John C.; Chavin, Kenneth; Morris-Stiff, Gareth; Warner, Susanne G.; Cardona, Kenneth; Fong, Zhi V.; Maker, Ajay; Libutti, Steven K.; Warren, Robert; St. Hill, Charles; Celinski, Scott; Newell, Philippa; et al.
Abstract: Background: Variation in the management of PNETs exist due to the limited high-level evidence to guide clinical practice. The aim of this work is to generate consensus guidelines with a Delphi process for managing PNETs. Methods: A panel of experts reviewed the surgical literature and scored a set of clinical case statements using a web-based survey to identify areas of agreement and disagreement. Results of the survey were discussed after each round of review. This cycle was repeated until no further likelihood of reaching consensus existed. Results: Twenty-two case statements related to surgical indications, preoperative biopsy, extent of resection, type of surgery, and tumor location were scored. Using a pre-defined definition of consensus, the panel achieved consensus on the following: i) resection is not recommended for <1 cm lesions; ii) resection is recommended for lesions greater than 2 cm; iii) lymph node dissection is recommended for radiographically-suspicious nodes with splenectomy for distal lesions; iv) tumor enucleation and central pancreatectomy are acceptable when technically feasible. No consensus was reached regarding issues of preoperative biopsy or 1–2 cm tumors. Conclusions: Using a structured, validated system for identifying consensus, an expert panel identified areas of agreement regarding critical management decisions for patients with PNET. Issues without consensus warrant additional clinical investigation.